Rare diseases - Open your heart and keep an open mind - Amaral, Olga (2018)
Lysosomal storage disorders (LSDs) are rare diseases which frequently have multisystemic involvement. Several of these pathologies affect the heart, among other organs. Well-known LSDs recognized to have cardiac involvement are Pompe, Danon, Fabry, some Mucopolysaccharidoses (MPSs), and Gaucher disease. Various cardiac symptoms may be observed including cardiomyopathy, coronary disease, and valvular disease. Nevertheless, coronary artery disease is also the leading cause of mortality and morbidity worldwide and its prevalence is expected to increase in the near future. Results obtained from research regarding the mechanisms of rare diseases may be extrapolated to other, more common, diseases increasing the application and impact of research in health care. Recent advances using cell models may allow the development of revolutionary methods to deal with these, and other, disorders. On one hand, we now have access to new sequencing approaches that allow rapid identification of the affected genes avoiding inadequate therapies and allowing the prediction of different responses to pharmaceutical agents. On the other hand, there are emerging molecular techniques that allow editing in order to better understand the mechanisms involved and possibly allow targeted and timely interventions. The future applications of biotechnology are certainly promising and, with genuine attentiveness and confidence, it may provide new solutions and deeper awareness of pathologies that affect a variety of different organs.